Bilateral Mooren’s Ulcer with perforation and Iris prolapse - Uday Gajiwala; Jyotsom Ganatra; Rajesh Patel; Parin Shah; Rohan Chariwala (Delhi Journal of Ophthalmology)
Mooren's Ulcer is an idiopathic, rapidly progressive, painful peripheral ulcerative keratitis with no associated scleritis. It's a diagnosis of exclusion which means all other diagnosable systemic disorders that could be responsible for the progressive destruction of cornea must be ruled out. The etiology of Mooren's Ulcer remains uncertain. However, recent studies indicate that it is an autoimmune disease directed against a specific target molecule in the corneal stroma, triggered in genetically susceptible individuals by one of several possible mechanisms. A 40 years old female presented to us on 25th January 2008 from rural tribal area of Sagbara with bilateral peripheral ulcerative keratitis with perforation and iris prolapse in right eye. She is known case of diabetes mellitus for last seven years. Diagnosis of Mooren's ulcer was made after she underwent extensive medical and laboratory testing to rule out an infectious or systemic cause of corneal melt. She benefited by right eye patch graft, left eye tissue adhesive with BCL application, Both eyes conjunctival peritomy and immunosuppressive drugs along with control of diabetes. This case report aims to highlight the diagnosis and treatment of Mooren's ulcer.